Perbandingan Pendekatan Manajemen Risiko Likuiditas antara Bank Umum Syariah dan Bank Pembiayaan Rakyat Syariah dalam Prespektif Regulasi OJK - Ramadhani, Miagasela Aprilia (Maliki Interdisciplinary Journal, 2025)
This study aims to identify and compare liquidity risk management strategies implemented by Islamic Commercial Banks (BUS) and Islamic Rural Financing Banks (BPRS) based on regulations set by the Financial Services Authority (OJK). Liquidity risk is a major challenge in maintaining the financial stability of Islamic banking, given the limited financial instruments that comply with sharia principles. BUS generally have broad access to Islamic money market instruments, such as Bank Indonesia Sharia Certificates (SBIS) and Islamic Interbank Money Market (PUAS), and implement a comprehensive diversification strategy of funding sources and Third Party Fund (DPK) management. In contrast, BPRS adopt a more conservative approach due to limited access to liquidity instruments, so they rely more on local customer deposits and internal networks. This difference has an impact on the level of financial resilience of both types of banks, both in the short and long term. OJK regulations are considered to have provided a proportional framework according to the characteristics of each bank, but challenges in implementation remain, especially for BPRS. These findings provide academic and practical contributions in encouraging the strengthening of the supervisory system and a more adaptive risk management strategy in Islamic banking in Indonesia.